2018
DOI: 10.4314/jae.v21i3.14
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of rural women entrepreneurs in non–farm and off–farm enterprises of households poverty reduction in Abia State

Abstract: The study assessed the contributions of rural women entrepreneurs in non-farm and off-farm enterprises to household poverty reduction in general merchandise (11.1%), restaurants/ bars (16.7 %), civil servants (4.4 %), and others (5.6 %) were identified as non-farm and off-farm enterprises. Income from non-farm and off-farm enterprises contributed to a very high extent and high extent (X =4.7, and4.5) and (X =4.4, 3.8 and 3.7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
(4 reference statements)
1
3
0
Order By: Relevance
“…Off-farm activities help the rural poor to complement yield and income from agriculture to meet the social welfare needs of their families. This finding lends credence to the submission of Obinna and Onu (2017) who reported that rural residents engage in off-farm activities to supplement income to reduce the risk associated with income generated solely from agricultural activities. The finding of the study also revealed that the coefficient of the self-help group (X7) was positive and significant at a 1% probability level.…”
Section: Determinants Of Poverty Among the Rural Farming Householdssupporting
confidence: 63%
“…Off-farm activities help the rural poor to complement yield and income from agriculture to meet the social welfare needs of their families. This finding lends credence to the submission of Obinna and Onu (2017) who reported that rural residents engage in off-farm activities to supplement income to reduce the risk associated with income generated solely from agricultural activities. The finding of the study also revealed that the coefficient of the self-help group (X7) was positive and significant at a 1% probability level.…”
Section: Determinants Of Poverty Among the Rural Farming Householdssupporting
confidence: 63%
“…The vast proportion of farmers that diversified into other economic activities can be ascribed to the limited land mass in South East Zone of Nigeria with the population competing for the little available arable land. Furthermore, Obinna and Onu (2017) opined that the meager income derived from farm enterprises compels households in rural African societies to engage in non-farm activities to supplement income, in order to lessen risk inherent in income from agricultural activities. He went ahead to explain that in places with limited land, the non-farm activities serve as vital economic option for the poor rural households.…”
Section: Economic Activities Engaged In By Farm Households In Southeast Nigeriamentioning
confidence: 99%
“…It was found that men were more creative as compared to women. Obinna and Ejike (2017) surveyed 180 respondents from Abia State of Nigeria using multi-stage sampling. The author recommended the formation of cooperative to encourage rural entrepreneurship.…”
Section: Overview Of Full Text Articlesmentioning
confidence: 99%
“…Rural areas are generally portrayed as backward, peripheral, deficit in entrepreneurial activities (Markantoni and Hoven, 2012). Academicians and governments focus on rural entrepreneurship as it symbolises innovations (Kabgu, 2018;Nosratabadi et al, 2020), selfemployment, reduces poverty (Obinna and Ejike, 2017;Osei and Zhuang, 2020), growth of economy (Kyrgidou and Petridou, 2013), and thus ensures dynamic and sustainable (Warren-Smith and Jackson, 2004) economies. In developing economies across the globe, it has been noted that rural women are engaged in child care activities (Markantoni and Hoven, 2012) and other household work.…”
Section: Introductionmentioning
confidence: 99%